A Liver Model of Infantile-Onset Pompe Disease Using Patient-Specific Induced Pluripotent Stem Cells - Yoshida, Takeshi; Jonouchi, Tatsuya; Osafune, Kenji; Takita, Junko; Sakurai, Hidetoshi (Frontiers in Cell and Developmental Biology, 2019)
Infantile-onset Pompe disease (IOPD) is a life-threatening multi-organ disease caused by an inborn defect of lysosomal acid α-glucosidase (GAA), which can degrade glycogen into glucose. Lack of GAA causes abnormal accumulation of glycogen in the lysosomes, particularly in the skeletal muscle, liver, and heart. Enzyme replacement therapy with recombinant human GAA (rhGAA) is the only available treatment; however, its effect varies by organ. Thus, to fully understand the pathomechanism of IOPD, organ-specific disease models are necessary. We previously generated induced pluripotent stem cells (iPSCs) from three unrelated patients with IOPD and establish a skeletal muscle model of IOPD. Here, we used the same iPSC lines as the previous study and differentiated them into hepatocytes. As a result, hepatocytes differentiated from iPSC of IOPD patients showed abnormal accumulation of lysosomal glycogen, the hallmark of Pompe disease. Using this model, we also demonstrated that glycogen accumulation was dose-dependently restored by rhGAA treatment. In conclusion, we have successfully established an in vitro liver model of IOPD using patient-specific iPSCs. This model can be a platform to elucidate the underlying disease mechanism or to be applied to drug-screening. Moreover, our study also suggest that an iPSC-based approach is suitable for modeling of diseases that affect multiple organs like Pompe disease.